Pengembangan Panduan Teknik Flooding dalam Konseling Behavioral untuk Mereduksi Fear of Missing Out Siswa Sekolah Menengah Atas - Wati, Ovita Dewi Sandra; Hotifah, Yuliati; Ramli, M (citeus, 2025)
Research and development in this study aim to produce a product of Flooding technique guidance in Behavior Counseling to reduce Fear of Missing Out of high school students who are theoretically and practically acceptable. The design of this study uses research and development steps: preliminary studies, product development, and product testing. The guide was tested using a Likert scale and concluded with the Aiken rater agreement analysis. The test results show that the Flooding technique guide has been theoretically and practically acceptable to reduce high school students' Fear of Missing Out.